The Art of Strategic Communication within Higher Education Institutions: A Case Study of Art Initiative at Stockholm School of Economics - Englund,Emma (2025)
This thesis uses the Stockholm School of Economics and its Art Initiative as a case study to investigate how institutional identity is strategically constructed through symbolic capital and aspirational narratives within higher education. Grounded in Bourdieu’s concept of symbolic capital and Christensen’s theory of aspirational communication, this research explores how symbolic practices, such as the integration of contemporary art, are employed to communicate institutional and emphatic values and strategically differentiate universities in an increasingly competitive academic landscape. By introducing the concept of aspirational capital, the study advances strategic communication theory by conceptualizing how future-oriented ideals function as rhetorical devices and communicative assets that shape legitimacy, perception, and organizational direction. Findings demonstrate that SSE’s Art Initiative operates as a symbolic distinction and that internal actors communicate the aspirations messages. By bridging sociological theory with strategic communication, this thesis offers insights into navigating the complexities of identity, legitimacy, and symbolic strategy in institutional branding.
Keywords: strategic communication; cultural capital; symbolic capital; aspirational talk; institutional branding; higher education; symbolic power